2019
DOI: 10.1042/bsr20191673
|View full text |Cite
|
Sign up to set email alerts
|

Moracin attenuates LPS-induced inflammation in nucleus pulposus cells via Nrf2/HO-1 and NF-κB/TGF-β pathway

Abstract: The present study was designed to investigate the protective effect of moracin on primary culture of nucleus pulposus cells in intervertebral disc and explore the underlying mechanism. Moracin treatment significantly inhibited the LPS-induced inflammatory cytokine accumulation (IL-1β, IL-6 and TNF-α) in nucleus pulposus cells. And moracin also dramatically decreased MDA activity, and increased the levels of SOD and CAT induced by LPS challenge. Moreover, the expressions of Nrf-2 and HO-1 were decreased and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Estrogen supplementation can enhance antioxidant capacity and correct redox imbalance stress 78 . In addition, the partial or whole functional deficiency of mitochondrial antioxidant enzymes is also critical in many other IDD processes induced by hyperosmolarity, mechanical overloading, AGE accumulation, or lipopolysaccharide 6,49,79,80 . The effects of biologically active components used to treat IDD have greatly improved in recent years.…”
Section: Mitochondrial Dysfunction and Idd Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen supplementation can enhance antioxidant capacity and correct redox imbalance stress 78 . In addition, the partial or whole functional deficiency of mitochondrial antioxidant enzymes is also critical in many other IDD processes induced by hyperosmolarity, mechanical overloading, AGE accumulation, or lipopolysaccharide 6,49,79,80 . The effects of biologically active components used to treat IDD have greatly improved in recent years.…”
Section: Mitochondrial Dysfunction and Idd Pathogenesismentioning
confidence: 99%
“…Jiao et al79 Hypertonic milieu NP cell culture Hyperosmolarity culture significantly decreased the total SOD activity compared with the in situosmolarity culture 79. Gu et al80 Lipopolysaccharides NP cell culture NP cells treated with LPS exhibited reduced SOD and catalase activity levels.80 Tang et al 81 H2O2/Honokiol NP cell culture Honokiol pretreatment significantly reversed the H2O2-suppressed expression of the SOD and Gpx1 genes.…”
mentioning
confidence: 99%
“…Surgically-induced OA models such as DMM and ACLT are the most commonly applied method of OA induction because of the ease by which the condition can be induced [ 143 , 151 ]. Moracin, a natural flavonoid compound extracted from Cortex Mori (the root bark of Morus alba ), is known for its anti-inflammatory activity via the suppression of NF-κB signaling pathway activation [ 207 , 208 ]. Moracin inhibits IL-1β-induced catabolic gene expression in rat primary chondrocytes through the inhibition of NF-κB signaling via Nrf2/HO1 activation.…”
Section: Pharmacological Treatment For Oa Protectionmentioning
confidence: 99%
“…Nrf2 can reduce the production of ROS from the source by maintaining mitochondrial homeostasis, thereby maintaining the redox balance in NP cells (Tang et al, 2019;Wang K. et al, 2019). Various drugs can inhibit IDD by activating the Nrf2 signaling pathway (Gu et al, 2019;Song et al, 2021;Wang K. et al, 2019;Wang et al, 2020a;Zhong et al, 2021). In this study, we confirmed that BARD increased the expression and nuclear translocation of Nrf2 and downstream HO-1 expression also significantly increased.…”
Section: Discussionmentioning
confidence: 99%